Analisis Biaya dan Profitabilitas Usaha Budidaya Kepiting di Desa Prapag Kidul - Dewi Uci; Mohamad Badrun Zaman (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2025)
This study examines the production costs and profitability of crab farming enterprises in Prapag Kidul Village, Brebes Regency. Using a quantitative descriptive approach, data were collected through in-depth interviews, field observations, and financial documentation from crab farmers. The research found that feed costs constitute the largest component of variable costs, accounting for 30% of total production costs. Financial analysis revealed favorable profitability levels with a Gross Profit Margin of 33%, Net Profit Margin of 24%, and Return on Investment of 30%. Factors significantly influencing profitability include cost management efficiency, market price fluctuations, crab quality, and access to capital. The findings suggest that systematic financial recording and cost management strategies are crucial for improving business sustainability and competitiveness in the crab farming sector.